Integrative analysis of Arabidopsis thaliana transcriptomics reveals intuitive splicing mechanism for circular RNA. Issue 20 (13th October 2016) - Sun, Xiaoyong; Wang, Lin; Ding, Jiechao; Wang, Yanru; Wang, Jiansheng; Zhang, Xiaoyang; Che, Yulei; Liu, Ziwei; Zhang, Xinran; Ye, Jiazhen; Wang, Jie; Sablok, Gaurav; et al.
Abstract : A new regulatory class of small endogenous RNAs called circular RNAs (circRNAs) has been described as miRNA sponges in animals. Using 16 Arabidopsis thaliana RNA‐Seq data sets, we identified 803 circRNAs in RNase R‐/non‐RNase R‐treated samples. The results revealed the following features: Canonical and noncanonical splicing can generate circRNAs; chloroplasts are a hotspot for circRNA generation; furthermore, limited complementary sequences exist not only in introns, but also in the sequences flanking splice sites. The latter finding suggests that multiple combinations between complementary sequences may facilitate the formation of the circular structure. Our results contribute to a better understanding of this novel class of plant circRNAs. Abstract :